The evolution of sentencing guidelines in Minnesota and England and Wales - Roberts, J (University of Chicago Press, 2019)
Sentencing guidelines were an exclusively American enterprise until recently. Since 2004, however, other countries have joined in. Contrasting approaches are exemplified by systems developed by the Minnesota Sentencing Guidelines Commission and the Sentencing Council of England and Wales. Minnesota’s guidelines are set out in grids that categorize cases by offense and criminal history. Each cell sets out ranges of sentences that are presumed to be appropriate. The English guidelines are step-by-step decision trees, one for each principal offense category. Each jurisdiction created an approach that fits its sentencing environment. The Minnesota grids are more restrictive and generate high levels of judicial conformity and consistency. The English guidelines allow greater discretion, possibly at the cost of consistency. However, the English approach provides ampler guidance on use of different dispositions, sentencing of multiple crimes, appropriate reductions to reflect guilty pleas, and other subjects. Neither the Minnesota Commission nor the English Council has been particularly self-critical. Minnesota’s main grid has changed little since 1980. England’s guidelines have evolved considerably, but the council has ignored calls to play a more active role in controlling the use of custody and hence the size of the prison population.